The optimization of abrasive wear behavior of fecrc coating composite with taguchi method - Yildiz, Tülay; Gür, Ali Kaya (My University, 2011)
Optimization of process parameters is the key step in the Taguchi Method to achieve high quality without increasing cost. The Taguchi method uses the orthogonal arrays to maximize the effect of controllable parameters and to minimize the effect of uncontrollable process parameters. In this study, FeCrC powder was alloyed on the surface of AISI 1030 steel with FeCrC powder having 70 % Cr ratio with the Plasma Transferred Arc Welding Method. In the coating process performed with the Plasma Transferred Arc Welding Method, N2 gas at 1-3-5% ratio was added to the shielding gas. The abrasive wear behavior of AISI 1030 substrate material whose surface was coated with high Cr in different atmospheres and the coating layer with high Cr were investigated under 5-10 N load and at 10-20 meter distances. The effect of wear loss on the lowest wear behavior, which is a most important criterion in determining the wear behavior, was optimized with the lowest-the best control characteristics of the Taguchi method and the results were analyzed with graphical methods.
Keywords: Analysis of variance; Plasma transferred arc coating; Surface modifications; Taguchi technique; Wear resistance